The life history and fishery assessment of largespot pompano, Trachinotus botla, in northern KwaZulu-Natal, South Africa - Parker, Denham (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2012)
Largespot pompano, Trachinotus botla, is a surf zone carangid with a cosmopolitan distribution in subtropical and tropical waters. Within South Africa, the species occurs along the KwaZulu-Natal coastline where it is a popular recreational fishing target. Recreational fishing in southern Africa has developed significantly in recent years, and is now regarded as an industry with huge economic potential. The long-term contribution of South African recreational fisheries to local economies is reliant upon sustainable exploitation through effective management. Trachinotus botla was found to grow rapidly with maximum observed age of six years. Otolith growth zone deposition was validated using edge analysis. Growth was similar between males and females until ~350 mm FL after which females continued to grow while growth in males slowed. The resulting overall sex ratio was slightly female-biased (1 male: 1.3 females). Trachinotus botla matures early with all fish considered to be mature at 290 mm FL, which corresponds to an age of three years. A protracted spawning season was observed ranging from November to February and there was evidence to suggest that T. botla is a serial spawner. Dietary analysis indicates that T. botla is an opportunistic predator with a catholic diet. The opportunistic utilization of "superabundant" prey items is a fundamental characteristic of the species feeding habits. An ontogenetic dietary shift was observed at approximately 300 mm FL that was linked to a shift in habitat preference. This thesis provided the first evidence that infection by the tongue-replacing isopod, Cymothoa borbonica, reduces the growth rate of wild host fish populations despite not affecting the diet, feeding habits and feeding frequency of their hosts. These results also highlighted the inadequacy of condition factor as a proxy for quantifying the effects of cymothoids on their hosts, and identified the need to incorporate host age when assessing the effects of parasite infection. Information on the life-cycle of C. borbonica, including estimates of the hypothesized "infectious" period and its longevity were obtained through analysis of parasite infection patterns as a function of host age and length. An assessment of the T. botla shore fishery of KwaZulu-Natal using historical catch data revealed that the fishery is stable. Productivity of the T. botla fishery increased towards the north of KwaZulu-Natal. Distinct seasonal variations in the T. botla fishery were also noted with catches peaking in summer months and lowest during winter. A per-recruit assessment revealed that the species is currently underexploited (SBR = 62% of pristine levels), and fishing mortality rate could be doubled before reaching the spawner biomass-per recruit target reference point of FSBâ‚„â‚€. A combination of the life history characteristics of species, the nature of the recreational shore fishery together with the current management regulation of 5 fish personâ »Â¹ dayâ »Â¹ has ensured the sustainable utilization of the T. botla resource in KwaZulu-Natal.
Keywords: Trachinotus -- South Africa -- KwaZulu-Natal; Carangidae -- South Africa -- KwaZulu-Natal; Fishing -- South Africa -- KwaZulu-Natal; Fishery management -- South Africa -- KwaZulu-Natal; Fishing -- Economic aspects -- South Africa -- KwaZulu-Natal; Fish stock assessment -- South Africa -- KwaZulu-Natal; Trachinotus -- Growth -- South Africa -- KwaZulu-Natal; Trachinotus -- Breeding -- South Africa -- KwaZulu-Natal; Trachinotus -- Food -- South Africa -- KwaZulu-Natal; Host-parasite relationships -- South Africa -- KwaZulu-Natal